Concise Construction of the ACDE Ring System of Calyciphylline A Type Alkaloids by a [5+2] Cycloaddition. Issue 37 (6th June 2019) - Nakamura, Hugh; Kawakami, Manami; Tsukano, Chihiro; Takemoto, Yoshiji
Abstract: A concise route for construction of the ACDE ring skeleton in calyciphylline A type alkaloids was developed using an intramolecular [5+2] cycloaddition reaction of an oxidopyrylium species bearing a tetrasubstituted olefin. Key to the success of this reaction was the combination of acid and base, which accelerated the construction of this skeleton containing a spiro ring and vicinal quaternary carbon centers. The resultant tricyclic ADE ring compound was converted to an ACDE ring model through C−H oxidation and an aza‐Wittig reaction. Abstract : A concise route to the ACDE ring skeleton of calyciphylline A type alkaloids was developed using the intramolecular [5+2] cycloaddition of an oxidopyrylium species bearing a tetrasubstituted olefin. This ring system containing a spiro ring and vicinal quaternary carbon centers was successfully constructed using a combination of acid and base to accelerate the reaction. The tricyclic ADE ring system was converted to the ACDE ring model through C−H oxidation and an aza‐Wittig reaction (see scheme).